Nonlinear causal dependencies as a signature of the complexity of the climate dynamics - S. Vannitsem; S. Vannitsem; X. S. Liang; X. S. Liang; C. A. Pires (Earth System Dynamics)
Nonlinear quadratic dynamical dependencies of large-scale climate modes are disentangled through the analysis of the rate of information transfer. Eight dominant climate modes are investigated, covering the tropics and extratropics over the North Pacific and Atlantic. A clear signature of nonlinear influences at low frequencies (timescales larger than 1 year) is emerging, while high frequencies are only affected by linear dependencies. These results point to the complex nonlinear collective behaviour at the global scale of the climate system at low frequencies, supporting earlier views that regional climate modes are local expressions of global intricate low-frequency-variability (LFV) dynamics, which are still to be fully uncovered.